Academic and Administrative Obstacles Facing Scientific Research in Higher Education Institutions in the Sultanate of Oman: An Analytical Quantitative Study - Karadsheh, Muneer; Al-Mawali, Nasser; Ali Rezaee, Abbas (DIRASAT: EDUCATIONAL SCIENCES, 2019)
The aim of this study was to investigate the most important academic and administrative obstacles facing scientific research in the Sultanate of Oman. It also aimed to reveal the impact of some independent variables, such as gender, age, type of institution, field of study, and country of education. The study was conducted on a sample of 714 researchers and academics working in institutions of higher education in various governorates of the Sultanate. The study is a descriptive research. A questionnaire was employed as the main instrument for data collection, devised analytically in line with the objectives and questions of the study, and to characterize and diagnose the phenomenon in a profound and comprehensive manner. The results of the study indicated that the most important administrative obstacles facing scientific research in the Sultanate is the large number of hours of teaching and the huge administrative loads. The results also showed that the lack of sabbatical leaves for the academics and the difficulty of obtaining them constitute the most important academic obstacle. The results revealed that the variables of the type of institution and the country of graduation are the most influential independent variables in the variances of views of academics and researchers about the academic and administrative obstacles they face while preparing for their scientific research.Keywords: Scientific Research, Administrative obstacles, Academic Obstacles